One‐Pot Synthesis of Dispiro[oxindole‐3, 3′‐pyrrolidines] by Three‐Component [3+2] Cycloadditions of in situ‐Generated Azomethine Ylides with 3‐Benzylidene‐2, 3‐dihydro‐1H‐indol‐2‐ones. Issue 11 (November 2013) - Matloubi Moghaddam, Firouz; Kiamehr, Mostafa; Reza Khodabakhshi, Mohammad; Jebeli Javan, Marjan; Fathi, Shaghayegh; Villinger, Alexander; Iaroshenko, Viktor O.; Langer, Peter
Abstract An efficient one‐pot, three‐component synthesis of novel dispiro[oxindole‐3, 3′‐pyrrolidines] by 1, 3‐dipolar cycloaddition of azomethine ylides, in situ generated by reaction of 1, 2‐diones with sarcosine and subsequent decarboxylation, with a series of (E)‐3‐benzylidene‐2, 3‐dihydro‐1H‐indol‐2‐ones is reported. Molecular complexity is generated in only one synthetic step. All reactions proceed with excellent regioselectivity and in good‐to‐excellent yields. The workup is easy, the reaction times are short, and no catalyst is required.